THE ADOPTION OF INTERNAL AUDITING STANDARD THAT AFFECTED THE EFFECTIVENESS OF RISK MANAGEMENT FOR INVESTMENT- PROMOTED BUSINESSES - นวลสอาด, วไลภรณ์; สุทธิสานนท์, อภิรดา (RMUTT Global Business and Economics Review, 2015)
This research aimed to explore information from investment-promoted businesses in the aspect of the adoption of Internal Auditing Standard that affected the effectiveness of risk management, and to study the relationship of the adoption of Internal Auditing Standard and the effectiveness of risk management for investment-promoted businesses. The sample in this study was 380 administrators from investment-promoted businesses in Bangkok and the suburban area. Statistics used to analyze data were Frequency, Percentage, Mean, Standard Deviation, Independent Samples t-test, One-way ANOVA, Pearson Correlation Analysis, and Multiple Regression Analysis. The results revealed that authorized capital and number of employees affected the effectiveness of risk management in the business strategy and business type aspects. The net asset value affected the effectiveness of risk management in the aspects of finance, operation, and control. Yearly net income affected the effectiveness of risk management in the operational aspect. The period of time operating the business affected the effectiveness of risk management in the financial aspect. The hypothesis results found that the adoption of Internal Auditing Standard, by using the forecasting method in all aspects, affected the priority level of the effectiveness of risk management in the aspects of strategy, finance, and operation. The adoption of Internal Auditing Standard correlated with the effectiveness of risk management in all aspects, where risk of strategic aspect was in the average level and same direction. Risks of financial, operational, and control aspects were in the low level and same direction.